Factors Influencing on Students’ Learning Problems at Primary School in Viengkham District, Luang Prabang Province - SILIVANH, Sommay; THIPPHAPHONE, Kinnaly; KEOHAVONG, Bounmy; CHOUMO, Yelee; KHOTSAIGNOH, Saiphone; PHETMANY, Somchit; PIEWKHAMPHOME, Sisaket; SIOUDOMPHANH, Vai (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)